2013
DOI: 10.2478/v10283-012-0039-x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Anatomical Variations of the Sinonasal Region and Chronic Rhino-Sinusitis: A Prospective Case Series Study

Abstract: Chronic rhinosinusitis is a chronic inflammation of the nasal and paranasal cavities. However, the main pathophysiology of these chronic conditions is poorly described and seems to be multifactorial.In the present study, we reviewed the computed tomography (CT) scans of patients with chronic rhinosinusitis to identify a probable association between the anatomical variations and chronic inflammation in the sinonasal region.Prospective study of the axial and coronal CT scans of 206 chronic rhinosinusitis patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
6
1
Order By: Relevance
“…Mamatha et al, Fadda et al and Madani et al correlated well with our study showing maxillary sinus to be the most common sinus involved. 18,20,25 Fadda et al observed in their study, statistical correlation between concha bullosa and maxillary sinusitis, between medial deviation of uncinate process and anterior ethmoid sinusitis, between agger nasi cells and frontal sinusitis and between septal deviation and maxillary sinusitis. 20 These correlations are similar to the ones found in our study.…”
Section: Discussionmentioning
confidence: 92%
“…Mamatha et al, Fadda et al and Madani et al correlated well with our study showing maxillary sinus to be the most common sinus involved. 18,20,25 Fadda et al observed in their study, statistical correlation between concha bullosa and maxillary sinusitis, between medial deviation of uncinate process and anterior ethmoid sinusitis, between agger nasi cells and frontal sinusitis and between septal deviation and maxillary sinusitis. 20 These correlations are similar to the ones found in our study.…”
Section: Discussionmentioning
confidence: 92%
“…Their clinical features, endoscopic and CT scan findings were studied in detail as per pretested proforma. 13 showed slight female preponderance of 51.7% and 51.4% respectively.In present study, the most common major factor seen in patients of chronic rhinosinusitis was nasal obstruction seen in 92 (88.46%) cases, followed by nasal discharge/post nasal drip in 84 (80.77%) cases. Least common presenting symptom was hyposmia or anosmia seen in 16 (15.38%) cases.…”
Section: Results and Observationmentioning
confidence: 98%
“…While in the study by Venkatachalam et al (2000) the commonest symptoms were nasal obstruction in 87%, nasal discharge in 70% of patients and the other symptoms were post nasal drip in 41% and abnormalities in sensation of smell in 36% of patients [12]. In another study by Nayak et al (1991) nasal discharge was the commonest complaint seen in 78.2%, while nasal blockage and headache was seen in 75.6% of patients [8] In our study patients bilateral maxillary sinusitis was seen in 24 patients (48%), unilateral maxillary sinusitis in 8 patients (16%), bilateral frontal sinusitis in 6 patients (12%), unilateral frontal sinusitis in 4 patients (8%), bilateral anterior ethmoidal sinusitis in 8 patients (16%), unilateral anterior ethmoidal sinusitis in 11 patients (22%), unilateral posterior ethmoidal sinusitis was seen in 9 patients(18%) and bilateral posterior ethmoidal sinusitis was seen in 5 patients ( 10%) and bilateral sphenoidal sinusitis was seen in 2 patients (4%). 3 patients had pansinusitis (6%)…”
Section: Discussionmentioning
confidence: 94%
“…[6,7] In the present study the incidence of DNS was more in male than female with an approximate ratio of 1.6:1 which is in agreement to a study done by Nayak et al . [8] In a study by Madani et al, there were 68.3% male and 31.7% female with a mean age of 29.13±15.21 years. [9] Ozkurt et al in his study observed that incidence was more in male as compared to female .…”
Section: Discussionmentioning
confidence: 99%